Phosphorus fertilization of 'Fuyutoyo' cabbages in phosphorus-rich Eutrustox soil - Cecilio Filho, Arthur Bernardes [UNESP]; Silverio da Silva, Gilson [UNESP]; Cortez, Juan Waldir Mendoza [UNESP] (Inst Investigaciones Agropecuarias, 2013)
Crop fertilization with P is a practice that constantly needs to be improved because of its high cost, natural reserve constraints, and environmental impact caused by the excessive use of nutrients. Phosphorus rates (0, 120, 240, 360, 480, 600, and 720 kg P2O5 ha(-1)) in the cultivation of 'Fuyutoyo' cabbage (Brassica oleracea L. var. capitata) in a P-rich Eutrustox soil (93 mg P dm(-3)) in Jaboticabal (21 degrees 15'22 '' S, 48 degrees 15'58 '' W; 575 m a.s.l.), Sao Paulo, Brazil, were evaluated in an experiment with a randomized complete block design with three replicates. Phosphorus rates influenced plant characteristics and soil P content. Maximum leaf and soil P content was obtained with 720 kg P2O5 ha(-1), but maximum values of leaf area, leaf dry mass, cabbage head mass, and productivity were obtained with 420, 310, 430, and 437.5 kg ha(-1) P2O5, respectively. Results indicate that even crops grown in a P-rich soil benefit from applying P fertilizer, which has a positive effect on the growth and productivity of the 'Fuyutoyo' cabbage.
Keywords: Brassica oleracea var. capitata; excess phosphorus; Plant nutrition